(untitled) (Pragyaratna प्रज्ञारत्न, 2025)
Nepal’s 2015 constitution introduced federalism as a mechanism to promote responsive and accountable local governance. Within this framework, the Local Government Institutional Self-Assessment, mandated by the Ministry of Federal Affairs and General Administration, functions as a key internal instrument enabling municipalities to evaluate their governance capacities, particularly accountability practices. This study investigates local government accountability through the Local Government Institutional Self-Assessment, mapping variations in performance across provinces and municipality categories, and critically assessing its effectiveness in advancing genuine accountability reforms. Employing secondary analysis of publicly available Local Government Institutional Self-Assessment reports from 2020 to 2024, the research examines how local governments document their accountability practices. A stratified sample of twenty-three municipalities comprising metropolitan, sub-metropolitan, municipal, and rural municipalities was selected based on initial reporting in fiscal year 2019/ 2020. Findings highlight notable disparities in accountability scores across provinces and municipality types, persistent deficiencies in grievance handling and audit implementation despite formal compliance, and a troubling disconnect between self-reported strengths and citizen dissatisfaction. The study concludes that the Local Government Institutional Self-Assessment, in its current design, risks perpetuating ritualistic compliance rather than fostering substantive accountability, particularly for marginalized communities. Policy recommendations emphasize revising the Local Government Institutional Self-Assessment indicators to better capture the quality of accountability practices, improving transparency in reporting, and strengthening the integration of self-assessment outcomes with targeted capacity-building initiatives.